The effectiveness of teaching reading narrative text by using advance organizer learning approach at the first years students of MAN 3 Kediri - Abdulloh, Awab (2020)
This research is aimed to know the effectiveness of teaching reading narrative text by using Advance Organizer at the first-year students of MAN 3 Kediri. The research is designed in experimental research which is using pretest and posttest as the data collection and the treatment to give the teaching material by using Advance Organizer. The result of study showed the significant difference between pre-test and post-test. By SPSS calculation, the mean is 24.737, the standard deviation is 24.521, standard error mean is 3.978, 95%, and the result of t-test by using SPSS 16.0 version is 6.219. The sig. 2-tailed shows 0, 000. It means that the result is significant in 1% significance level. So, it can be concluding that learning reading narrative text by using Advance Organizer at the first-year students of MAN 3 Kediri is effective. The result of this study recommended for the teacher to give the suitable technique to teach reading. Then, the content of the study can be recommendation for the next researcher.